Production Parameters of Three Varieties of Red Onion Origin of Botanical Seed Applied With Auxin - Nurjannah Ruslan; Elkawakib Syam'un; Feranita Haring (International Journal of Agriculture System, 2023)
Shallots are one of the horticultural commodities that are highly expected to be cultivated intensively. The need for shallots nationally increases from year to year. These needs cannot be increased by increasing national production. One thing that can be done to make shallots available is to use good varieties and provide growth regulators with auxin using botanical seeds (True Shallot Seed) as a seed source. This study aims to determine the effect of the interaction between varieties with auxin concentration on the growth and production of shallots. This research was carried out in the Exfam Land, Faculty of Agriculture, Hasanuddin University, Makassar, South Sulawesi Province, from August to November 2021. This study used a Split plot design which consisted of two factors, the first factor as the main factor being different plant varieties, namely Lokananta, Maserati, and Sanren. While the sub-plot is the concentration of Auxin consisted of 4 levels, namely 0 mg L-1,100 mg L-1, 200 mg L-1, and 300 mg L-1 . The experimental results showed that the red onion variety using the variety with a concentration of 200 mg L-1 gave the best results on the fresh weight of shallots (123.80 g), the dry weight of shallots (93.77 g), the tuber weight of (86.63 g/plot), tuberproduction (4.51 kg/plot), and productivity (19.50  ton ha-1). The treatment of shallot varieties using the Sanren variety gave the best results on the parameters of the number of bulbs (1.89 bulbs). The application of auxin at a concentration of 300 mg L-1 gave the best results on the tuber diameter parameter of 28.42 mm.